Coping with sexual difficulties: the lived experience of women taking selective serotonin reuptake inhibitor (SSRI) medication - O'Mullan, Catherine (Curtin University, 2015)
This study used Interpretive Phenomenological Analysis to explore women’s experiences of coping with the sexual side effects of selective serotonin reuptake inhibitors (SSRIs). Coping strategies included searching; suffering in silence; trying to resolve; and accepting what is. The findings emphasise the need to recognise and address psychological, social and cultural factors which may influence how women cope with sexual side effects, and underline the need for a multidisciplinary management approach that moves beyond biomedical interventions.